Obediências e transgressões nas vivências da sexualidade - Andrea Cristina Martelli (Ciências Sociais Unisinos)
This study deals with the imaginary of sexuality of teachers of the early years of elementary school and it is based on a doctoral research project. Out of the questions raised in our research project, in this text we chose to discuss whether teachers, in their experiences of sexuality, discover new paths or just live according to the institutional principles acquired during their lives. As a research methodology, we work with Life Oral History and Thematic Oral History. Our theoretical framework was based mainly on the works of Michel Maffesoli. We conducted interviews with teachers, who told about their lives guided by a specific theme: the experiences of their sexuality. The analysis of the narratives showed us that, on the one hand, religion and family are significant marks in the imaginary of sexuality of these teachers, but, on the other hand, they have built, over the course of their lives, imperceptible escapes and clever ways to avoid the institutional principles acquired over time. In other words, the teachers experience their sexualities in movement between obedience and transgression.